Time Resolved Photometric and Spectroscopic Analysis of Chemically Peculiar Stars. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Joshi, Santosh; Joshi, Gireesh C.; Joshi, Y. C.; Aggrawal, Rahul
Abstract: Here we present the report on the "Nainital–Cape survey" research project aiming to search for and study the pulsational variability of main-sequence chemically peculiar (CP) stars. For this study, the time-series photometric observations of the sample stars were carried out at the 1.04 m ARIES telescope (India), while the high-resolution spectroscopic and spectro-polarimetric observations were carried out at the the 6.0 m Russian telescope. Under this project, we have recently found clear evidence of photometric variability in the Am star HD 73045, which is likely to be pulsating in nature with a period of about 36 min, hence adding a new member to the family of the δ Scuti pulsating variables that have peculiar abundances.